(untitled) (The Journal of Ad-din Women’s Medical College, 2023)
Introduction: To understand of the epidemiological trend in the inpatient department (IPD), it is important for health care planning, appropriate management allocation & improving existing services facilities. Therefore, this study was done to evaluate the disease pattern of children in IPD of the Pediatric unit at Shaheed Sayed Nazrul Islam Medical College & Hospital, where children came from grass root level at Kishoreganj, Bangladesh. Methods & Materials: This was a descriptive type of observational study. The patient came to the pediatric IPD from February 1 to July 31, 2022, six months were analyzed. Face to face interview was done through a semi structured questionnaire. Results: A total of 724 children were enrolled during this study period. Infant 67%, total under five 83% and more than five years old was 17% of all children. Acute Respiratory tract infection was 59% and among them Pneumonia was 24%, Bronchiolitis 65%. Acute watery diarrhea was most common (8%) within GIT morbidities and eenteric fever (4%). Forty-three (6%) children suffered from Central Nervous System (CNS) diseases. Most children (n-29) suffered from Nephrotic syndrome and Acute Glomerulo Nnephritis was only 03 in count. It is important to mentioned that some patients had no disease whereas they admitted on the interest of their parents. Female (14%) were less than the male baby and 82% were Muslim. Conclusion: Most were preventable diseases. Children suffered mostly respiratory problems and among them Bronchiolitis was the number one illness. Prevalence of AWD was more in GIT problems. The disease frequency of this study will help to understand the depth and pattern of the problem. The Journal of Ad-din Women’s Medical College; Vol. 10 (2), July 2022; p 21-24